Odpowiedź :
[tex]a) \\\frac9{10}+\frac12-\frac35-\frac7{20}=\frac{18}{20}+\frac{10}{20}-\frac{12}{20}-\frac7{20}=\frac9{20}[/tex]
[tex]b) \\2\frac12*8-6*0.3=\frac52*8-6*\frac3{10}=5*4-2*\frac{3}{5}=20-\frac{6}5=18\frac{10}{5}-\frac65=18\frac45[/tex]
[tex]c)\\4-0,27*3=4-0,81=3,19[/tex]
[tex]d) \\2\frac25:0,15=\frac{12}{5}:\frac{15}{100}=\frac{12}5*\frac{100}{15}=12*\frac{20}{15}=\frac{240}{15}=16[/tex]
[tex]e) \\9:\frac{5}{29}-1=9*\frac{29}{5}-1=\frac{261}{5}-1=\frac{261}{5}-\frac55=\frac{256}{5}=51\frac12[/tex]
[tex]f) \\5-\frac13*0,7=5-\frac13*\frac7{10}=5-\frac7{30} = \frac{150}{30}-\frac7{30}=\frac{143}{30}=4\frac{23}{30}[/tex]
Od a) do c) :
[tex]a] \ \frac{9}{10}+\frac{1}{2}-\frac{3}{5}-\frac{7}{20}=\frac{18}{20}+\frac{10}{20}-\frac{12}{20}-\frac{7}{20}=\frac{18+10-12-7}{20}=\frac{9}{20}\\\\b] \ 2\frac{1}{2}\cdot8-6\cdot0,3=\frac{5}{2}\cdot8-1,8=5\cdot4-1,8=20-1,8=18,2\\\\c] \ 4-0,27\cdot3=4-0,81=3,19[/tex]
Od d) do f) :
[tex]d] \ 2\frac{2}{5}:0,15=\frac{12}{5}:\frac{15}{100}=\frac{12}{5}:\frac{3}{20}=\frac{\not12^4}{5}\cdot\frac{20}{\not3_1}=\frac{80}{5}=16\\\\e] \ 9:\frac{5}{29}-1=9\cdot\frac{29}{5}-1=\frac{261}{5}-\frac{5}{5}=\frac{256}{5}=51\frac{1}{5}\\\\f] \ 5-\frac{1}{3}\cdot0,7=5-\frac{1}{3}\cdot\frac{7}{10}=5-\frac{7}{30}=4\frac{23}{30}[/tex]